Development of a wearable glove for virtual reality application - Low, Ze Xian (2023)
In recent years, as entered the era of 5G and the Internet-of-things (IoT), significant developments have been made in human-machine interfaces (HMIs) that enable more intuitive interactions between humans and the digital world. However, the current glove-based HMI solutions available in the market have limitations due to non-conformal sensor integration, which constrains finger movement. To address this issue, this project proposes a haptic-feedback glovebased HMI with a graphene thread sensor, ESP-NOW for wireless connection, a haptic actuator, and MPU6050 accelerometers. The graphene thread exhibits a sensitivity of 700 Ω/° and the graphene thread sensors show no deterioration for 100 cycles. Furthermore, in this project, the detection of multidirectional bending events in virtual space using the piezoresistive signals for various degrees of freedom on the human hand has been demonstrated. This project also perform haptic mechanical stimulation via motor vibration to realize the augmented HMI. Through the integrated demonstration of multidimensional manipulation and haptic feedback, our glove shows its potential as a promising solution for advanced human-machine interaction. It can benefit diversified areas, including entertainment, home healthcare, sports training, and the medical industry.